Internalised stigma in adults with autism: A German multi-center survey. (June 2019) - Bachmann, Christian J.; Höfer, Juliana; Kamp-Becker, Inge; Küpper, Charlotte; Poustka, Luise; Roepke, Stefan; Roessner, Veit; Stroth, Sanna; Wolff, Nicole; Hoffmann, Falk
Highlights: In this study, 15.4% of adults with ASD reported moderate or severe stigma. Age ≥35 years and low educational level predicted a higher level of stigma. Compared to other mental disorders, stigma in ASD appears to be lower. Abstract: The aim of this study was to evaluate the extent of internalised stigma and possible predictors in adults with a diagnosis of autism spectrum disorder (ASD). We measured internalised stigma in a sample of 149 adults with ASD and an IQ ≥70 (79.2% male, mean age 31.8 years), using the Brief Version of the Internalized Stigma of Mental Illness Scale (ISMI-10). The mean ISMI-10 score was 1.93 (SD=0.57), with 15.4% of participants reporting moderate or severe internalised stigma. Moderate or severe stigma was more frequent in persons aged ≥35 years (OR: 4.36), and in individuals with low educational level (OR: 6.00). IQ, sex and ASD diagnostic subtype (ICD-10) did not influence stigma severity. Compared to other mental disorders, the level of internalised stigma in adults with ASD without intellectual disability appears to be lower.